Realization Of Preventive Functions Of Criminal Punishment Through The Institute Of Exemption - Gulaina Osmanova, Aizhan Ryssaldiyeva, Gulzat Zhunisbayeva,; Magauova, Akmaral; Kuatova, Aida (Opción, 2019)
The aim of the study is to investigate the realization of preventive functions of criminal punishment through the institute of exemption via comparative qualitative research methods. As a result, the efficiency of the penal correction system of the state depends on its activity. In conclusion, it is necessary that the penal correction system worked fairly and lawfully as the main organizational basis on increase in efficiency of the realization of preventive functions of criminal punishments in order that preventive function of criminal punishment worked effectively.